2011
DOI: 10.11606/s1413-95962011000400006
|View full text |Cite
|
Sign up to set email alerts
|

Participação dos nervos intercostais na inervação do diafragma de gatos (Felis catus, Linnaeus, 1758)

Abstract: ResumoO objetivo do presente trabalho foi avaliar a inervação do músculo diafragma em gatos, proveniente dos nervos intercostais, contradizendo diversos autores que afirmam ser este músculo inervado apenas pelos ramos dos nervos frênicos direito e esquerdo. Foi observado que existe a frequência de nervos dispostos entre o 8º e o 11º espaços intercostais.Palavras-chave: Gato. Diafragma. Nervos intercostais. AbstractThe knowledge of organism's anatomy is essential to conduct any experiment or study with itself. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…[6][7][8][9][10][11][12][13] On the other hand, our findings are in agreement with other studies that pointed out the contribution of the intercostal nerves to the innervation of the diaphragm. 4,5,[14][15][16][17][18][19] We observed the innervation of the diaphragm by the intercostal nerves 6 to 12, mainly by the 8 th nerve. Rosenblueth et al (1961), 4 even if they observed the participation of the intercostal nerves 4 to 10, observed that the major intercostal nerve acting in the innervation of the diaphragm was the 8 th nerve.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8][9][10][11][12][13] On the other hand, our findings are in agreement with other studies that pointed out the contribution of the intercostal nerves to the innervation of the diaphragm. 4,5,[14][15][16][17][18][19] We observed the innervation of the diaphragm by the intercostal nerves 6 to 12, mainly by the 8 th nerve. Rosenblueth et al (1961), 4 even if they observed the participation of the intercostal nerves 4 to 10, observed that the major intercostal nerve acting in the innervation of the diaphragm was the 8 th nerve.…”
Section: Discussionmentioning
confidence: 99%
“…In dogs, MELO et al (1999) 24 observed the innervation of the diaphragm by the intercostal nerve pairs 8 to 12 in 93.54% of cats and dogs. Faria et al (2011) 16 observed the central innervation of the diaphragm by the intercostal nerves 9 through 11, but the possible participation of the nerve fibers from the intercostal nerves 7, 8, and 12. Oliveira et al (2001) 25 observed that the diaphragm of hybrids of bovines and zebus received the innervation of the intercostal nerves 7 through 12 in 50% of the animals; from the intercostal nerves 6 through 12 in 33.3%; from the left antimere of the 6 th intercostal nerve in 13.3% of the animals, and from the right antimere of the 7 th nerve in 3.3% of the animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phrenic nerve is the main motor supply of the diaphragm, and it is composed, in most domestic species, by ventral branches of the fifth, sixth and seventh cervical spinal nerves (Ghoshal, 1986). However, diaphragm can also be innervated by intercostal nerves, as observed in dogs, cats (Dyce et al, 2017; Faria et al, 2011; Ghoshal, 1986) and guinea pigs ( Cavia porcellus , Linnaeus, 1758) (Faria et al, 2019).…”
Section: Introductionmentioning
confidence: 99%